TRAINING IN WRITING JOURNAL ARTICLES AND USING TECHNOLOGY FOR PUBLICATION IN REPUTABLE JOURNALS - Riyanti, Dwi; Dewantara, Jagad Aditya; Yansa, Hemri; Chorina, Malisa (LPPM Univ. Ibn Khaldun Bogor, 2024)
The current community service was aimed at providing training for lecturers regarding publications in nationally and internationally reputable journals. Although in recent years, lecturers' publications have increased, many lecturers still do not know how to use technology to support their publications. Using presentation and sharing methods accompanied by question and answer sessions, the community service has a target for lecturers in teacher training and education faculty, Universitas Tanjungpura. Forty-nine lecturers participated in this activity. Considering that the COVID-19 pandemic was not completely over, this community service activity was carried out in a hybrid way. Offline activities were held in the FKIP Untan Hall, while the online ones were through ZOOM. The outputs of this training were that the lecturers became more familiar and used technology that can be used to support their publications scientific publications.